The structure of risk in selected elements of labour-market policy reform - Zybała, Andrzej (Journal of Public Governance, 2015)
The text analyses labour-market policy reforms implemented in Poland since mid-2014. The author focuses on their attendant structure of risks, particularly those seen in the part of the reform that envisages the delivery of professional activation services for the long-term unemployed by private contractors (employment agencies). The author discusses the traditional risks inherent in this type of reform found in a number of countries that have implemented it for a long time. These are: ‘creaming’ (selection by service providers of which clients to serve), ‘parking’ (less effort put into working with beneficiaries who are harder to place) and ‘gaming’ (exploitation of loopholes in programme design). The impact of these risks depends on the construction of quasi-markets in which the providers operate. The author argues that the success of reforms in Poland depends on the capacity to manage such risks, which, due to its very nature, is a skill that is hard to develop, and identifies a range of attendant difficulties. They arise, among others, from the adopted quasi-market model and from the current model of public management in the area of labour market policy.